Evaluasi Kinerja Alat Ukur Tinggi Muka Air Otomatis Menggunakan Kalibrator Di Laboratorium - Isnan Fauzan Akrom; Hany Agustiani (Pusat Litbang Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2018)
Water resources infrastructure development requires a careful planning, one of which requires hydrological analysis. The accuracy of hydrological data is influenced by the method, operator/observer, and the performance of the measuring instrument. Up date water resources management agencies in Indonesia have conducted observations of discharges in the rivers or channels, by observing Water Level (WL) at the gauging station. WL values can be read directly or by using an automatic WL meter tools (AUTO) which have been finstalled in many gauging stations. Therefore, it is necessary to evaluate the AUTO performance that can be done through calibration in the laboratory. This paper evaluates the performance of several types of AUTO (AWLR, AWLL buoyance, and AWLL pressure) by comparing themeasurement results with the standard/reference tool i.e, using a calibrator instrument, so that the values of the measurement error and uncertainty were obtained. Both parameters were used to determine the performance of AUTO devices because they are related to the level of accuracy and precision. Based on the results, it was found that AWLR produces the best level of accuracy and precision, followed by AWLL pressure, and AWLL buoyance.